2005
DOI: 10.1016/j.mod.2004.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Six1 is not involved in limb tendon development, but is expressed in limb connective tissue under Shh regulation

Abstract: Mice deficient for the homeobox gene Six1 display defects in limb muscles consistent with the Six1 expression in myogenic cells. In addition to its myogenic expression domain, Six1 has been described as being located in digit tendons and as being associated with connective tissue patterning in mouse limbs. With the aim of determining a possible involvement of Six1 in tendon development, we have carefully characterised the non-myogenic expression domain of the Six1 gene in mouse and chick limbs. In contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 53 publications
4
73
0
Order By: Relevance
“…5A-F). Consistent with previous studies, we found that Scx induction in the forming autopod and zeugopod of Sp d muscle-less embryos was not significantly affected up to E12.5 (Bonnin et al, 2005;Schweitzer et al, 2001); however, the differentiation and maintenance of the zeugopod tendon progenitors were impaired in the absence of muscles, leading to complete loss of tendons and tendon progenitors from the zeugopod by E13.5 (Fig. 5G,H) (Bonnin et al, 2005).…”
Section: Integration Of the Autopod And Zeugopod Developmental Prograsupporting
confidence: 92%
See 2 more Smart Citations
“…5A-F). Consistent with previous studies, we found that Scx induction in the forming autopod and zeugopod of Sp d muscle-less embryos was not significantly affected up to E12.5 (Bonnin et al, 2005;Schweitzer et al, 2001); however, the differentiation and maintenance of the zeugopod tendon progenitors were impaired in the absence of muscles, leading to complete loss of tendons and tendon progenitors from the zeugopod by E13.5 (Fig. 5G,H) (Bonnin et al, 2005).…”
Section: Integration Of the Autopod And Zeugopod Developmental Prograsupporting
confidence: 92%
“…The muscle dependency of limb tendons was also evaluated in the mouse using the Splotch (Sp) mutant, in which disruption of the Pax3 gene results in failure of myoblast migration, thus generating muscle-less limbs (Bober et al, 1994). Similar to chick embryos, in muscle-less Sp embryos limb tendon progenitor induction was not affected but tendon progenitors subsequently failed to differentiate (Bonnin et al, 2005;Schweitzer et al, 2001). It was therefore suggested that mouse tendon development can be divided into two stages: a progenitor, muscleindependent stage followed by a differentiated, muscle-dependent stage (Bonnin et al, 2005;Tozer and Duprez, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm that mSim2-expressing cells in limbs were myogenic cells, we took advantage of the existence of Pax3-deficient mice, in which no myogenic cells are detected in the limbs (Relaix et al, 2003). In the absence of muscle cells, muscle connective tissue and tendons initiate their development normally, showing the absence of muscle requirement for other limb tissue formation at early stages of development (Kardon, 1998;Kardon et al, 2003, Bonnin et al, 2005. Consequently, the absence of gene expression in early Pax3 mutant limbs (before E12) strongly suggests that it is not an indirect consequence of the sion of the Sim1 and Sim2 genes and different steps of limb muscle formation, in chick and mouse.…”
Section: B C D E Fmentioning
confidence: 99%
“…The probes were detected by an alkaline phosphatase-coupled antibody against digoxigenin using nitroblue tetrazolium/5-bromo-chloro-3-indolyl phosphate (NBT/BCIP) as the chromogenic susbstrate for alkaline phosphatase. Antisense digoxigeninlabelled RNA probes were prepared as described: chick Pax3, chick MyoD, and mouse MyoD (Delfini and Duprez, 2004;Tozer et al, 2007); chick and mouse Scleraxis (Bonnin et al, 2005); mouse Pax3 (Relaix et al, 2003); chick Sim1 (Pourquié et al, 1996) and Sim2 ; mouse Sim1 (Michaud et al, 1998) and Sim2 (Goshu et al, 2002).…”
Section: In Situ Hybridisation To Tissue Sections or To Wholemount Emmentioning
confidence: 99%